Environmental Risk Factors, Larval Indices, and Dengue Prevention Behaviors in Pelita Village, Samarinda Ilir District, Indonesia - Nadhirah Shahira Nur; Suryani Noer Wahyudi; Emilia Sophie Tandiera; Siswanto (Universitas Mulawarman, 2026)
Dengue Hemorrhagic Fever (DHF) remained a major public health problem in Indonesia, with 114,720 reported cases and 894 deaths in 2023. In the working area of Sidomulyo Primary Health Center, DHF cases increased from 21 cases in 2023 to 68 cases in 2024. This study aimed to describe environmental risk factors, larval presence, and dengue prevention behaviors among residents of Pelita Village, Samarinda Ilir District. A quantitative study with a cross-sectional design was conducted using a rapid epidemiological survey approach from April to May 2026. A total of 210 respondents were selected through cluster sampling from 30 clusters. The results showed that 97.62% of respondents had never experienced DHF, while 27.62% reported close contact with DHF patients. The Larvae Free Index was 52.38%, substantially below the national target of 95%. Most respondents demonstrated good knowledge, attitudes, and perceptions regarding dengue prevention; however, mosquito larvae, potential breeding sites, and several suboptimal preventive practices were still identified. It was concluded that environmental and behavioral factors potentially supporting DHF transmission remained present in Pelita Village, highlighting the need to strengthen mosquito breeding site control programs and sustain community participation.